Fibroids and natural fertility: a systematic review and meta-analysis. Issue 1 (July 2021) - Somigliana, Edgardo; Reschini, Marco; Bonanni, Valentina; Busnelli, Andrea; Li Piani, Letizia; Vercellini, Paolo
Abstract: Available evidence from IVF studies supports a detrimental effect of submucosal and intramural fibroids on embryo implantation. It is misleading, however, to infer evidence obtained in IVF settings to natural fertility. Therefore, a systematic review and meta-analysis was conducted on the effect of fibroids on natural fertility. Studies comparing fertile and infertile women, and those investigating whether the presence of fibroids was a risk factor, were reviewed, as well as studies comparing women with and without fibroids. The aim was also to establish whether the frequency of infertility differed between the two groups. Seven out of 11 selected studies did not aim to establish whether fibroids caused infertility but, rather, whether a history of infertility could be a risk factor for fibroids. A meta-analysis of the four remaining studies that concomitantly evaluated the presence of fibroids and infertility studies highlighted a common odds ratio of fibroids in subfertile women of 3.54 (95% CI 1.55 to 8.11). When focusing on the two most informative studies, i.e. the studies comparing time to pregnancy in women with and without fibroids, the common OR was 1.93 (95% CI 0.89 to 4.18). In conclusion, the association between fibroids and infertility has been insufficiently investigated. Epidemiological studies suggest, but do not demonstrate, that fibroids may interfere with natural fertility. Given the high prevalence of these lesions in women seeking pregnancy, further evidence is urgently needed.